Pelvic Ultrasound Imaging-Based Prevalence of Gynecological Morbidity in a Population of Asymptomatic Reproductive-Age Women Attending a Healthcare Outreach Program in the Andaman and Nicobar Islands of India - Rajput, Eesha (Indian Journal of Radiology and Imaging, 2023)
Gynecological morbidity in the reproductive age is defined as any condition, disease, or dysfunction of the reproductive system that is not related to pregnancy, abortion, or childbirth. Common gynecological symptoms include irregular menstruation, white vaginal discharge, burning urination, itching of the vulva, inguinal swelling, and nonmenstrual bleeding or spotting and chronic pelvic pain. Masses of the reproductive tract, adnexal masses, and polycystic ovary syndrome also occur in the reproductive age group. Gynecological disease contributes to nearly 4.5% of the overall global disease burden and exceeds the prevalence of other major global diseases such as malaria, tuberculosis, ischemic heart disease, and maternal conditions. Ultrasound is a painless, noninvasive imaging modality that can be used for the detection of gynecological abnormalities. This study uses pelvic ultrasound imaging to estimate the prevalence of gynecological morbidity in a population of asymptomatic reproductive-age women attending a healthcare outreach program in the Andaman and Nicobar Islands of India.
Keywords: ultrasound; fibroids; cyst; Andaman and Nicobar Islands; pelvic ultrasound; screening